Validated LC-ESI-MS/MS method for the determination of ivosidenib in 10 µL mice plasma: application to a pharmacokinetic study - Sreekanth Dittakavi; Rakesh Kumar Jat; Sadanand Rangnathrao Mallurwar; Ravi Kumar Jairam; Ramesh Mullangi (International Association of Physical Chemists (IAPC), 2019)
A simple, selective and rapid LC-ESI-MS/MS method has been developed and validated for the quantification of ivosidenib in mice plasma using warfarin as an internal standard (I.S.) as per regulatory guideline. Sample preparation was accomplished through a simple protein precipitation process. Chromatography of ivosidenib and the I.S. was achieved on an Atlantis dC18 column using an isocratic mobile phase comprising 0.2 % formic acid in water and acetonitrile (25:75, v/v) delivered at a flow rate of 1.0 mL/min. LC-MS/MS was operated under the multiple reaction-monitoring mode (MRM) using the electrospray ionization technique in positive ion mode and the transitions of m/z 583.1→186.1 and m/z 309.2→251.3 were used to quantitate ivosidenib and the I.S, respectively. The total chromatographic run time was 2.0 min. Linearity was established in the concentration range of 1.10-3293 ng/mL (r2>0.99). The intra- and inter-day accuracy and precision for ivosidenib in mice plasma were in the range of 5.72-9.91 and 5.90-10.7 %, respectively. Ivosidenib was found to be stable on bench-top for 6 h, up to three freeze-thaw cycles, in in-injector for 24 h and for one month at -80 °C. The applicability of the validated method has been demonstrated in a mice pharmacokinetic study. Following intravenous (2 mg/kg) and oral (5 mg/kg) administration of ivosidenib to mice, concentrations were quantifiable up to 24 and 48 h, respectively. The bioavailability was 61 %.